Screening of selected polyphenol compounds in palm oil mill effluent (POME) - Sharif, Mohd. Faez (2009)
Total antioxidant activities and phenolic contents of raw and treated POME extracts (rPOME and tPOME respectively) were investigated. The total antioxidant activity was estimated using DPPH (2,2-diphenyl-1-picrylhydrazyl) assay. The total phenolic contents were measured using Folin-Ciocalteu assay. Thin layer chromatography and reversed-phase high-performance liquid chromatographic (RP-HPLC) separation methods with UV spectrophotometric detection were also used for the determination of compound of interest in POME extracts. Identification was based on retention times and UV spectra by comparison with commercial standards. The standards used were Gallic acid, Resveratrol, Quercetin and Kaempferol. The extracts were analyzed after extraction with ethanol. Resveratrol were identified in the rPOME while no detection of any four of the standards was showed in the tPOME. From the study, rPOME was clearly shown to have higher antioxidant activities and total phenolic contents than the tPOME. The highest percentage inhibition of the DPPH by rPOME was 89.5% and the total phenolic content measured was 6.5 mg of gallic acid equivalents (GAE). In conclusion, palm oil mill effluent could potentially become an alternative source of antioxidant